Ibrutinib inhibits collagen-mediated but not ADP-mediated platelet aggregation - Kamel, S; Horton, L; Ysebaert, L; Levade, M; Burbury, K; Tan, S; Cole-Sinclair, M; Reynolds, J; Filshie, R; Schischka, S; Khot, A; Sandhu, S; et al. (Leukemia, 2015)
The BTK (Bruton’s tyrosine kinase) inhibitor ibrutinib is associated with an increased risk of bleeding. A previous study reported defects in collagen- and adenosine diphosphate (ADP)-dependent platelet responses when ibrutinib was added ex vivo to patient samples. Whereas the collagen defect is expected given the central role of BTK in glycoprotein VI signaling, the ADP defect lacks a mechanistic explanation. In order to determine the real-life consequences of BTK platelet blockade, we performed light transmission aggregometry in 23 patients receiving ibrutinib treatment. All patients had reductions in collagen-mediated platelet aggregation, with a significant association between the degree of inhibition and the occurrence of clinical bleeding or bruising ( P =0.044). This collagen defect was reversible on drug cessation. In contrast to the previous ex vivo report, we found no in vivo ADP defects in subjects receiving standard doses of ibrutinib. These results establish platelet light transmission aggregometry as a method for gauging, at least qualitatively, the severity of platelet impairment in patients receiving ibrutinib treatment.